A Randomized Controlled Trial of Group Triple P With Chinese Parents in Mainland China. (November 2016) - Guo, Mingchun; Morawska, Alina; Sanders, Matthew R.
This study evaluated the effects of Group Triple P with Chinese parents on parenting and child outcomes as well as outcomes relating to child academic learning in Mainland China. Participants were 81 Chinese parents and their children in Shanghai, who were randomly allocated to an intervention group or wait-list control group. Parents in the intervention condition received Group Triple P training, and parents and children were assessed at three/two time points. Compared with the control group, parents in the intervention group reported significant improvements in child adjustment problems, parenting practices, parental adjustment, and parenting self-efficacy at post-assessment. Moreover, there was a significant increase in parents' satisfaction with children's academic achievement and a reduction in children's academic problem behaviors at post-intervention. All these effects were maintained at 6-month follow-up. There was also a significant increase in the child report of positive parenting at post-intervention.